LITERATURE STUDY: IMPLEMENTATION OF CHEMISTRY LEARNING USING BLENDED LEARNING MODEL TO IMPROVE STUDENTS' HOTS (HIGHER ORDER THINKING SKILLS) - Badrus Syamsi; Ade Suryanda (JURNAL EDUSCIENCE, 2023)
This study aims to determine the effect of implementing chemistry learning using the blended learning model in increasing student HOTS. The method used in this research is literature study. The data collection technique used, namely collecting data by finding sources and creating them through primary sources such as books, journals and existing research. The results showed that learning chemistry using a blended learning model could increase students' HOTS. Chemistry learning using a blended learning model can shape students to study individually either in groups, face to face, or online, and to solve problems, identify, interpret, and communicate learning outcomes.Keywords: Blended learning, HOTS, Chemistry LearningÂ AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh implementasi pembelajaran kimia menggunakan model blended learning dalam meningkatkan HOTS siswa. Metode yang digunakan dalam penelitian ini, yaitu studi literatur. Teknik pengumpulan data yang digunakan, yaitu mengumpulkan data dengan cara mencari sumber dan mengkreasikannya melalui sumber primer seperti buku, jurnal dan penelitian yang ada. Hasil penelitian menunjukkan bahwa pembelajaran kimia menggunakan model blended learning dapat meningkatkan HOTS siswa. pembelajaran kimia menggunakan model blended learning dapat membentuk siswa untuk belajar secara individu baik dalam kelompok, tatap muka, atau online, dan untuk memecahkan masalah, mengidentifikasi, menginterpretasikan, dan mengkomunikasikan hasil belajar.Kata Kunci: Blended learning, HOTS, Pembelajaran Kimia